Fatal encephalitis caused by free-living amoebas in an infant from Piura, Peru - Mori-Llontop, Laura Melissa (2025)
Free-living amoeba encephalitis usually causes severe disease with high mortality despite appropriate management. We present the case of a 7-month-old infant from northern Peru who had a 10-day illness characterized by irritability, hypoactivity, gaze deviation, and drowsiness. Both cerebrospinal fluid analysis and brain biopsy revealed structures compatible with free-living amoebae. Molecular analysis by PCR was ultimately negative for Acanthoameba sp. and Ballamuthia sp. Molecular analysis of CSF is important to identify the amoeba species involved.